Using GIS to understand the relationship of community factors and police shootings in the United States: a First Look - Arslan, Hasan (2016)
While many municipalities and counties have good collections of crime data, the lack of availability of national data limits the potential research on gun violence related to officer-involved shootings. Using an open source data collection data model, a data repository of police shootings is being created (SHOT - Statistics Help Officer Training). With incident location information, this paper takes a “first look” at understanding community factors and their relationship to police “use of force”. The paper will briefly describe how GIS has been used to study crime, the problem related to data and data collection for police shootings and the SHOT method of data collection. Preliminary results of a GIS analysis of incidents, income, diversity and education will be described